All-Fiber OAM Amplifier With High Purity and Broadband Spectrum Gain Based on Fused Taper Vortex-Beam Coupler - Jianxiang Wen (IEEE Photonics Journal, 2018)
All-fiber orbital angular momentum (OAM) amplifier with high purity and broadband spectrum gain based on a fused taper vortex-beam coupler (VBC) has been studied. Active and passive few-mode fibers (FMFs), which have similar geometric parameters, are fabricated. A VBC using a single-mode fiber and a passive FMF is designed and fabricated. The VBC can generate the first-order OAM in the range of 1480-1640 nm and its purity up to 91%. Then, an all-fiber vortex amplification system is constructed for the first time, and the first-order OAM is amplified using this system with a low-gain difference (ΔG). The gain exceeds 22 dB at 1549 nm, and its full width at half maximum is approximately 40 nm: 1519-1559 nm. This is a novel all-fiber OAM amplification system with a simple structure and low cost that is applicable in optical communication fields.